Optimization of Fruit DNA Extraction by Kitchen Kit Method with Isopropanol and Absolute Ethanol - Umi Kulsum Nur Qomariah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
soft fruits are high-value food commodities that are in great demand by the wider community, so they have the potential to be developed. It is necessary to study various scientific disciplines, one of which is the molecular biology approach. DNA is a basic element in molecular biology research. The DNA extraction technique greatly determines the quality and quantity of the DNA produced. The chemical solvent used in the precipitation is an important factor in producing the quality and quantity of DNA, so optimization is required. The purpose of the research to investigate the effect of isopropanol and ethanol on fruit DNA extraction. The DNA extraction method used is the kitchen kit method which is used on 4 types of soft fruit: papaya, guava, banana and strawberry. The principles of DNA extraction are lysis, precipitation and purification. The lysis process was carried out chemically with a solution of detergent and NaCl, and physically by means of a blender, then separation was carried out using filter paper. The aquos phase is collected to be chemically precipitated. Precipitation was carried out with cold absolute ethanol and cold isopropanol at -40C. The results of extraction with isopropanol showed the consistency and quantity of fruit DNA: papaya had rather dense fiber, slightly soft guava, slightly faded thin strawberry and rather dense fibrous banana. The results of absolute ethanol extraction showed the consistency of fruit DNA: papaya fiber rather dense, guava fiber medium, strawberry rather dense and banana fiber moderate. DNA extraction by ethanol precipitation produces more optimal DNA compared to isopropanol precipitation.